2015
DOI: 10.1214/14-aap1060
|View full text |Cite
|
Sign up to set email alerts
|

The set of solutions of random XORSAT formulae

Abstract: The XOR-satisfiability (XORSAT) problem requires finding an assignment of n Boolean variables that satisfy m exclusive OR (XOR) clauses, whereby each clause constrains a subset of the variables. We consider random XORSAT instances, drawn uniformly at random from the ensemble of formulae containing n variables and m clauses of size k. This model presents several structural similarities to other ensembles of constraint satisfaction problems, such as ksatisfiability (k-SAT), hypergraph bicoloring and graph colori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Further, in the physics literature it was suggested that the core could be characterised by means of a "message passing" algorithm called Warning Propagation [22,Chapter 18]. A simple inductive argument shows that the k-core coincides with the fixed point of Warning Propagation on G. In [14] this description of the 2-core of hypergraphs was used to characterise the clustering phenomenon in the solution space of random XORSAT instances. The Warning Propagation description of the core will play a key role in the present paper.…”
Section: Background and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, in the physics literature it was suggested that the core could be characterised by means of a "message passing" algorithm called Warning Propagation [22,Chapter 18]. A simple inductive argument shows that the k-core coincides with the fixed point of Warning Propagation on G. In [14] this description of the 2-core of hypergraphs was used to characterise the clustering phenomenon in the solution space of random XORSAT instances. The Warning Propagation description of the core will play a key role in the present paper.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In order to study the set of solutions of random k-XORSAT formulas Ibrahimi, Kanoria, Kraning and Montanari [14] used Warning Propagation describe the local structure of the 2core in random hypergraphs by means of a random marked tree. They showed that the local structure can be described as the limit of Warning Propagation on a suitable Galton-Watson tree.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in a recent paper [10] we combined Warning Propagation with a fixed point analysis on Galton-Watson trees to the k-core problem. A similar approach was used in [24] in the context of random constraint satisfaction problems. Further, in [4] Warning Propagation was applied to the random graph coloring problem.…”
Section: Further Related Workmentioning
confidence: 99%